Pengaruh Komitmen Manajemen dan Kapasitas Sumber Daya Manusia Terhadap Transparansi Laporan Keuangan di Pt. Hilon Felt Cabang Mojokerto - Amin, Muhammad Shodiqul; Supriadi, Supriadi; Isnaini, Nurdiana Fitri (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
This research aims to know the influence of the commitment of the management capacity of human resources to the implementation of the transparency of financial reporting in the PT. Hilon Felt Mojokerto. Type of this research is quantitative research. The population in this study are all employees of the PT. Hilon Felt Mojokerto. Samples were taken using the technique of sampling as much as 36 total respondents. Engineering data collection using the questionnaire by means of distributed to respondents. Technique of data analysis in research using multiple linear regression analysis. Hypothesis testing using simultaneous test (test F) and partial test (test t) hypothesis testing using simultaneous test (test F) and partial test (test t) using SPSS program version 23.0. Research results based on the validity of the Test showed that the entire instrument of research is said to be valid and reliability. Based on results of test of hypothesis shows that simultaneously obtained significant levels of test results F = 0.000 < 0.05 (level of significant) and partially independent variables data obtained (commitment human resource capacity management) has the value of the significance result < 0.05  so that can be expressed the independent variable by partially and simultaneous effect on the transparency of financial statements. Based on the value of beta coefficient indicates the variable capacity of most influential human resources significantly to transparency of the financial report with the greatest value i.e. 4.14